Paddy's health response analysis to thermal radiation emits by power transmission line / Aida Syahindah Ruzaini - Ruzaini, Aida Syahindah (2018)
Recently threat to crop health are observed by exposure of the crop to the thermal radiation. The power transmission line are the big structure that known gives the thermal radiation. It became one of the factor that may influence the crop health. This study was to analyses the paddy's health affected by the exposure. There are various type of power line. This study used high voltage power line, 115 kV which composed of seven single cable. The conventional method from previous research is limited to analyses the large cover area as they performed experiment in laboratory. Therefore, remote sensing method is be able to overcome those. It offers fast processing computer based method. Two type of satellite images used which are Sentinel 2 and Landsat 8. Sentinel 2 were used to analyze the paddy's health by Normalized Difference Vegetation Index (NDVI) and emission of thermal radiation is detect using Landsat 8 by Land Surface Temperature (LST). Both are processed in Erdas software then map and analyze in ArcGIS software. This study are for 2 years observation during paddy's growth. Therefore, the study reveals that thermal radiation from the power line did effect to paddy health. It is found that R-squared value of correlation are 0.2083 for 2 m distance of paddy field with power line in year 2016 and increase with 0.3326 for year 2017. However, the relationship are weak and it is not the main factor that contributes to paddy healthiness. This research benefit to related party such as MADA or farmer himself, considering that remote sensing is easy and suitable method for them to analyse paddy's health effectively